Tantangan Pertanian Berkelanjutan di Indonesia: Suatu Tinjauan Lingkungan Hidup - Hammada, Mortaza A Syafinuddin (Jurnal Ekologi, Masyarakat dan Sains, 2024)
This text is preliminary research on the challenges of sustainable agriculture in Indonesia. The research aims to provide an opinion on the main challenges of the agricultural sector when viewed from an environmental science perspective. Criticism of agricultural management is in line with humanity's concerns about the failure of the concept of modern industrialization in controlling the rate of environmental degradation. The challenge of the agricultural sector was originally to double land productivity, but now it has changed to land sustainability with production remaining stable. The method for writing this manuscript is library research, namely collecting various scientific references and analyzing them using the content analysis method. The conclusion of this research is that Indonesian agriculture has challenges in four main quadrants, namely farmer professional competence, agricultural institutions, government policies and social movements.